Bending as Key Mechanism in the Tactile Perception of Fibrillar Surfaces. Issue 4 (20th December 2021) - Gedsun, Angelika; Sahli, Riad; Meng, Xing; Hensel, René; Bennewitz, Roland
Abstract: The touching of fibrillar surfaces elicits a broad range of affective reactions, which range from the adverse stinginess of a stiff bristle brush to the pleasant feel of velvet. To study the tactile perception of model fibrillar surfaces, a unique set of samples carrying dense, regular arrays of cylindrical microfibrils with high aspect ratio made from different elastomer materials have been created. Fibril length and material compliance are varied independently such that their respective influence on tactile perception can be elucidated. This work finds that the tactile perception of similarity between samples is dominated by bending of the fibrils under sliding touch. The results demonstrate that variations of material stiffness and of surface structure are not necessarily perceived independently by touch. In the case of fibrillar elastomer surfaces, it is rather the ratio of fibril length and storage modulus which determines fibril bending and becomes the dominant tactile dimension. Visual access to the sample during tactile exploration improves the tactile perception of fibril bendability. Experiments with colored samples show a distraction by color in participants' decisions regarding tactile similarity only for yellow samples of outstanding brightness. Abstract : The interaction between surface fibrils and the skin of the fingertip determines the tactile perception of materials such as velvet. Psychophysical experiments with a unique set of samples made from different elastomers reveal that fibril length and material compliance are not perceived independently, the tactile perception of similarity between samples is rather dominated by the bending of fibrils.